2019
DOI: 10.1080/14616734.2019.1582595
|View full text |Cite
|
Sign up to set email alerts
|

Is one secure attachment enough? Infant cortisol reactivity and the security of infant-mother and infant-father attachments at the end of the first year

Abstract: Attachment security is theorized to shape stress reactivity, but extant work has failed to find consistent links between attachment security to mothers and infant cortisol reactivity. We examined family configurations of infant-mother and infant-father attachment security in relation to infant cortisol reactivity. One-year old infants (N = 180) participated in the Strange Situation with mothers and fathers in two counterbalanced lab visits, one month apart (12 and 13 months). Infants with secure attachments on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 78 publications
0
15
0
Order By: Relevance
“…In humans, decreased responsiveness, sensitivity, and synchrony in early caregiving have been correlated with prolonged or exaggerated increases in cortisol in response to stress (118, 119), whereas secure parental attachment has been associated with lower cortisol levels in response to stress (120) ( Figure 1 ). However, in cases of more severe early deprivation or maltreatment, patterns of HPA responsiveness have been mixed, perhaps due to the complex nature of maltreatment and the co-occurrence with psychiatric disorders.…”
Section: Pathways To Addictionmentioning
confidence: 99%
“…In humans, decreased responsiveness, sensitivity, and synchrony in early caregiving have been correlated with prolonged or exaggerated increases in cortisol in response to stress (118, 119), whereas secure parental attachment has been associated with lower cortisol levels in response to stress (120) ( Figure 1 ). However, in cases of more severe early deprivation or maltreatment, patterns of HPA responsiveness have been mixed, perhaps due to the complex nature of maltreatment and the co-occurrence with psychiatric disorders.…”
Section: Pathways To Addictionmentioning
confidence: 99%
“…The SSP involves physical separations between parent and infant and is often conducted during the latter half of the first year to assess the security of infant-parent attachments. Even though such separations between 12-month-old infants and their caregivers reliably elicit stress (Kuo et al, 2019;Spangler & Grossmann, 1993), infants of this age are becoming more independent as they enter toddlerhood, feeling more comfortable exploring further away from their caregiver for longer periods of time, and developing more mature emotion and behavioral regulation strategies than younger infants. Young infants of around 4 to 6 months of age are more dependent on the caregiver to direct interaction and respond to affective and behavioral cues as has been so elegantly demonstrated in studies using the SFP.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Whereas most research to date has focused on mother-infant adrenocortical attunement, few studies have considered cortisol attunement between infants and their fathers, even though infants form attachment relationships with their fathers (Kuo et al, 2019). Prior research has demonstrated oxytocin synchrony between fathers and infants, suggesting transmission in the neurobiology of affiliation (Feldman, 2012b;.…”
Section: Father-infant Cortisol Attunementmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrasting findings were also reported by studies that compared the significance of the parent's identity (mostly mothers and fathers) on the child's developmental outcomes. Some studies showed that secure attachment to mothers only may confer more favorable outcomes than secure attachment to fathers only (e.g., when assessing cortisol output; Kuo et al, 2019); yet other studies indicated that the difference in the predictive power of having a single secure attachment to mothers as opposed to fathers is immaterial (e.g., when assessing externalizing behavior problems; Kochanska & Kim, 2013).…”
Section: Research On Attachment Network: a Brief Historymentioning
confidence: 99%